Para a≠-3 e a≠3, a expressão a²+6a+9/3 ÷ a²-9/a-3 equivale a:
a) a+3/3
b) a+2
c) a+3
d) a-3
Usuário anônimo:
Qual o motivo da denúncia?
Soluções para a tarefa
Respondido por
19
R: Letra A
veja
![\frac{a^2+6a+9}{3} \div \frac{a^2-9}{a-3} = \frac{a^2+6a+9}{3} \div \frac{a^2-9}{a-3} =](https://tex.z-dn.net/?f=+%5Cfrac%7Ba%5E2%2B6a%2B9%7D%7B3%7D+%5Cdiv+%5Cfrac%7Ba%5E2-9%7D%7Ba-3%7D+%3D)
![\frac{(a+3)^2}{3} \times \frac{a-3}{(a+3(a-3)} = \frac{(a+3)^2}{3} \times \frac{a-3}{(a+3(a-3)} =](https://tex.z-dn.net/?f=+%5Cfrac%7B%28a%2B3%29%5E2%7D%7B3%7D+%5Ctimes+%5Cfrac%7Ba-3%7D%7B%28a%2B3%28a-3%29%7D+%3D)
cancela a-3 com a-3 e a+3 com a+3
fica
![\frac{a+3}{3} \frac{a+3}{3}](https://tex.z-dn.net/?f=+%5Cfrac%7Ba%2B3%7D%7B3%7D+)
veja
cancela a-3 com a-3 e a+3 com a+3
fica
Perguntas interessantes
Ed. Física,
1 ano atrás
História,
1 ano atrás
Sociologia,
1 ano atrás
Geografia,
1 ano atrás
Geografia,
1 ano atrás
História,
1 ano atrás
Matemática,
1 ano atrás